2011
DOI: 10.2147/ibpc.s9486
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and other morbidities with Cushing’s syndrome associated with corticosteroids: a review

Abstract: Corticosteroids constitute an ideal treatment for various inflammatory and autoimmune disorders due to their anti-inflammatory and immunomodulatory actions. However, corticosteroids have a considerable number of side effects, including hypertension, diabetes, lipid disorders, sleep apnea, osteoporosis, myopathy, and disorders of coagulation and fibrinolysis, which are components of Cushing’s syndrome (CS). Corticosteroid-induced side effects are dependent on the formulation, route, dose, and time of exposure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 127 publications
0
19
1
5
Order By: Relevance
“…2,3 Pharmaceutical treatments include corticosteroids and immunosuppressive agents that help control the disease, but impair immunity resulting in increased risk of infection. 4,5 Prior studies highlighted the importance of immunizations by demonstrating the benefits of influenza vaccination in MG patients. 6 Influenza-like illnesses and pneumonia lead to worsened MG exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Pharmaceutical treatments include corticosteroids and immunosuppressive agents that help control the disease, but impair immunity resulting in increased risk of infection. 4,5 Prior studies highlighted the importance of immunizations by demonstrating the benefits of influenza vaccination in MG patients. 6 Influenza-like illnesses and pneumonia lead to worsened MG exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated that high prevalence of MetS among these patients might be the consequence of certain pharmacologic interventions, particularly of chronic corticosteroid therapy [43]. However, the presence of MetS in as much as 16% of 1494 young (35.2+13.4 years) SLE patients with rather short disease duration (24.1+18.0 weeks) seems to be enough to reject this relationship as causal [2].…”
Section: Metabolic Syndrome In Patients With Antiphospholipid Syndrommentioning
confidence: 99%
“…GC were shown to support S324 Puzserova and Bernatova Vol. 65 vasoconstriction as they increase the response to NA, angiotensin II and other vasoconstrictors (Grunfeld et al 1985, Walker and Edwards 1994, Saruta 1996, Ullian 1999, Peppa et al 2011). Saruta (1996 found that the number of AT 1 receptors of vascular smooth muscle cells is significantly increased by GC.…”
Section: No and Hpa Axis Interaction In Stressmentioning
confidence: 99%
“…Thus GC may alter NO release from the endothelium, CNS and perivascular nervous system. In addition, corticosteroidinduced metabolic abnormalities, such as hyperglycemia, excess liberation of free fatty acids, increased plasma levels of triglycerides, insulin resistance and hyperinsulinemia exert pathological impact on endothelial function and appear to contribute to the corticosteroid-induced hypertension (Peppa et al 2011.…”
Section: No and Hpa Axis Interaction In Stressmentioning
confidence: 99%